2011 International Conference on Electromagnetics in Advanced Applications 2011
DOI: 10.1109/iceaa.2011.6046467
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency scaling of the mixed MFIE for scatterers with a non-simply connected surface

Abstract: -The Magnetic Field Integral Equation (MFIE) is a widely used integral equation for the solution of electromagnetic scattering problems involving perfectly conducting objects. It is usually discretized by means of RWG functions as both basis and test functions. This discretization of the MFIE is well-known for its good condition number. However, it is equally well-known for the inferior accuracy of its solution when compared to the Electric Field Integral Equation (EFIE). What is less-known is that this accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
(13 reference statements)
2
16
0
Order By: Relevance
“…For each wave number, the smallest singular value was plotted in Figure 3. Again, the result is as expected from [7].…”
Section: Numerical Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…For each wave number, the smallest singular value was plotted in Figure 3. Again, the result is as expected from [7].…”
Section: Numerical Resultssupporting
confidence: 77%
“…Indeed, it was shown that a mixed discretization scheme, in which the MFIE is tested using rotated Buffa-Christiansen (BC, [2]) or Chen-Wilton (CW, [3]) functions, delivers a much better accuracy [4,5] than the standard discretization scheme. In addition, the mixed discretization yields physical solutions at low frequencies [6,7], which is in stark contrast to the standard scheme. A drawback of the mixed scheme is the need for a barycentrically refined mesh, which increases the number of triangle-triangle interactions that needs to be evaluated for each impedance matrix element.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The new operator will be discretized by adopting a mixed-discretization strategy [7,8] where the magnetic operators are tested with Buffa-Christiansen (BC) basis functions. For the sake of brevity we consider a discretization for the case of simply connected structures; minor modifications are required for the non-simply connected case.…”
Section: Discretization Strategymentioning
confidence: 99%
“…If these two components are not separated during the solution process, numerical cancelations that deteriorate the accuracy of the far field computation ensue. This phenomenon has been first pointed out in [24], and further studied in [25], [26] and [27] and [28]. The reader should be aware of the meaning of "very low frequency" in this context.…”
mentioning
confidence: 99%